Brain-Derived Neurotrophic Factor (BDNF) Role in Cannabinoid-Mediated Neurogenesis - Ferreira, Filipa Fiel; Ribeiro, Filipa F.; Rodrigues, Rui S.; Sebastião, Ana Maria; Xapelli, Sara (Frontiers in Cellular Neuroscience, 2018)
The adult mammalian brain can produce new neurons in a process called adult neurogenesis, which occurs mainly in the subventricular zone (SVZ) and in the hippocampal dentate gyrus (DG). Brain-derived neurotrophic factor (BDNF) signaling and cannabinoid type 1 and 2 receptors (CB1R and CB2R) have been shown to independently modulate neurogenesis, but how they may interact is unknown. We now used SVZ and DG neurosphere cultures from early (P1-3) postnatal rats to study the CB1R and CB2R crosstalk with BDNF in modulating neurogenesis. BDNF promoted an increase in SVZ and DG stemness and cell proliferation, an effect often blocked by a CB2R selective antagonist. CB2R selective activation promoted an increase in DG multipotency, which was inhibited by the presence of a BDNF scavenger. CB1R activation induced an increase in SVZ and DG cell proliferation, being both effects dependent on BDNF. Furthermore, SVZ and DG neuronal differentiation was facilitated by CB1R and/or CB2R activation and this effect was blocked by sequestering endogenous BDNF. Conversely, BDNF promoted neuronal differentiation, an effect abrogated in SVZ cells by CB1R or CB2R blockade while in DG cells it was inhibited by CB2R blockade. We conclude that endogenous BDNF is crucial for the cannabinoid-mediated effects on SVZ and DG neurogenesis. On the other hand, cannabinoid receptor signaling is also determinant for BDNF actions upon neurogenesis. These findings provide support for an interaction between BDNF and endocannabinoid signaling to control neurogenesis at distinct levels, further contributing to highlight novel mechanisms in the emerging field of brain repair.